2017
DOI: 10.1016/j.bbmt.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Incidence of Secondary Malignancies after Allogeneic Hematopoietic Cell Transplantation: A Single-Center Experience

Abstract: To review the emergence of secondary malignancies (SMs) in recipients of allogeneic hematopoietic cell transplantation (HCT), we documented the occurrence of SMs in 2415 allogeneic HCT recipients, ages 18 to 71, in a single center over 4 decades. SMs were seen in 209 patients, including 58 with nonmetastatic squamous cell (SCC) and basal cell carcinoma (BCC) of the skin. Cumulative incidence of SM was 6.3% at 10 years, 13.5% at 20 years, and 17.6% at 30 years post-HCT. Median age at diagnosis of SMs was 61 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Interestingly, it has been reported that the 5‐year OS rates after the diagnosis of solid cancer in HCT recipients were not different from patients non‐transplant patients who developed de novo solid cancers, 25 indicating that the natural history of malignancies in HCT recipients is similar to that of the general population. Although the presence of prior secondary malignancy did not significantly alter the survival of our study cohort, the incidence of secondary malignancies in HCT recipients is known to be higher than the general population 12,24 . In addition, the estimated incidence of secondary malignancy rises in every decade after allogeneic HCT 26 .…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Interestingly, it has been reported that the 5‐year OS rates after the diagnosis of solid cancer in HCT recipients were not different from patients non‐transplant patients who developed de novo solid cancers, 25 indicating that the natural history of malignancies in HCT recipients is similar to that of the general population. Although the presence of prior secondary malignancy did not significantly alter the survival of our study cohort, the incidence of secondary malignancies in HCT recipients is known to be higher than the general population 12,24 . In addition, the estimated incidence of secondary malignancy rises in every decade after allogeneic HCT 26 .…”
Section: Discussionmentioning
confidence: 59%
“…The overall survival after the diagnosis of the secondary malignancy (excluding non-metastatic SCC/BCC of skin) was 63% at 3 years post-HCT, 58% 5 years post-HCT, and 50% 10 years post-HCT. 24 The overall survival after the diagnosis of secondary malignancy was dependent on the allogeneic HCT recipients' ECOG score at diagnosis of the secondary malignancy, with low ECOG associated with improved survival. 24 Interestingly, it has been reported that the 5-year OS rates after the diagnosis of solid cancer in HCT recipients were not different from patients non-transplant patients who developed de novo solid cancers, 25 indicating that the natural history of malignancies in HCT recipients is similar to that of the general population.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations